If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -13 = 2x + 3y Reorder the terms: -13 + 4x = 2x + 3y Solving -13 + 4x = 2x + 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -13 + 4x + -2x = 2x + -2x + 3y Combine like terms: 4x + -2x = 2x -13 + 2x = 2x + -2x + 3y Combine like terms: 2x + -2x = 0 -13 + 2x = 0 + 3y -13 + 2x = 3y Add '13' to each side of the equation. -13 + 13 + 2x = 13 + 3y Combine like terms: -13 + 13 = 0 0 + 2x = 13 + 3y 2x = 13 + 3y Divide each side by '2'. x = 6.5 + 1.5y Simplifying x = 6.5 + 1.5y
| 1017.36=3.14r^2 | | 8+x*8+x=27*12 | | 5x/8x-64 | | 6q^2-2q=5q^2-5q+18 | | 29+n=57 | | 1017.33=3.14r^2 | | 4c-19=-3(e+4) | | f(x)=x^3+7x^2+4x-12 | | 0.5(m-6)=12 | | -x+2y=15.5 | | 140=(x-2)/x*180 | | Y=-0.03x^2+2.4X | | 6(1+4y)-4y=1 | | 17-(2m+7)=4+4m-18 | | 0=-x^2+202x-5000 | | 5u+5v-5(5u-4v+4w)= | | (a-18)2/3-8=56 | | Ln(y)=0.77 | | A+12=3A-96 | | 3b-9=b+5 | | 30x+44=25x+99 | | 6(2/3×-10) | | (21x+6)*2=180 | | g(x)=x^2-3/4x-7/64 | | 9495.36=3.14x*12 | | 0.13-0.03(x+2)=-0.01(1-x) | | e-132/3=-19 | | -3(x+2)-5=-3x-11 | | 100-(5x+16)=5(x+8)+x | | 66x+110=1100 | | T^2-t/6-35/6=0 | | X^2+y=24 |